2016
DOI: 10.1177/0954406215608892
|View full text |Cite
|
Sign up to set email alerts
|

Bearing life prognosis based on monotonic feature selection and similarity modeling

Abstract: In data-driven prognosis approach, indicator information plays an important role for reliable prediction. Although lots of researches have been carried out on prognosis algorithms, only few have paid attention on developing an effective method to select ‘good’ degradation indicators. This paper presents a novel strategy to address the problem, which mainly proposes methods of monotonic feature selection using rank mutual information, and similarity-based modeling for remaining life estimation. The proposed sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The result was verified with the published literature. [31][32][33] The crack propagation effect was verified with the published article on the same. 38 The bearing B2-2 HDIE curve is shown in Figure 13(a) and (b).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The result was verified with the published literature. [31][32][33] The crack propagation effect was verified with the published article on the same. 38 The bearing B2-2 HDIE curve is shown in Figure 13(a) and (b).…”
Section: Resultssupporting
confidence: 62%
“…The highly monotonic features are used for the detection of fault in bearing as it is treated as an effective feature for calculation of bearing degradation. Recent publications [31][32][33][34] have suggested the frequency domain feature for the prediction of degradation in gear and bearings. The selected fault feature vectors are being applied as an input vector to the GTM.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Therefore, in this paper the authors have included several frequency-domain features that have been applied successfully for condition monitoring of bearings and gears in the recent few years. 18,[31][32][33] The list of features and their computational formulae are listed in Table 1. As far as the authors' knowledge, this feature set is being used first time with SOM.…”
Section: Theory Of Svrmentioning
confidence: 99%
“…The techniques recommended in papers did not require the establishment of threshold for RUL estimation. Niu et al 18 suggested a new approach for monotonic feature selection based on rank mutual information and utilised the concept of similarity modeling for RUL prediction of bearings. The research papers indicate that a monotonic feature is desirable for accurately determining the RUL, which is another big challenge in bearing prognostics.…”
Section: Introductionmentioning
confidence: 99%
“…The operating conditions of the test bench are as follows: The motor speed is 1800 rpm. The sampling frequency is 25.6 kHz sampling, and a radial force of 4000N is applied to the rotating shaft and the bearing to be tested [ 77 ].…”
Section: Experimental Studymentioning
confidence: 99%